Analisis dan Rancang Bangun Jaringan Komunikasi VOIP Dengan Server Briker Pada SMKN 1 Tanjung Jabung Timur - Yunarti, Welaspen; Roestam, Rusdianto (Jurnal Manajemen Sistem Informasi, 2018)
SMKN 1 Tanjung Jabung Timur has had internet network infrastructure, but its usage is not maximum specifically for using local line as alternative media to communicate freely. VoIP (Voice Over Internet Protocol) technology is used as communication line that are not paid (free) and open source can provide a cheaper communication alternative solution. This technology is able to pass voice traffic, video and data in the form of packets over an IP network.The methodology of research conducted, is devided by two, the study of literature and experimental . Chatting system is a system that is used for conversation among computers Smartphone, Smartphone to Smartphone in a network so that the system will be very efficient and economical. This chatting system uses Linphone application (open source) to communicate via online among users. Merging VoIP technology that uses Briker and chatting technology with Linphone can be used to support the activities of employees or students in SMKN 1 Tanjung Jabung Timur. In addition, this technology can shorten the time in communication among departments in SMKN 1 Tanjung Jabung Timur, especially SMKN 1 Tanjung Jabung Timur that has not had IP phone at each department. So communication among sections or among students can occur as efficiently and economically as possible in SMKN 1 Tanjung Jabung Timur environment can be achieved.